(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The increasing implementation of Distributed Generation in power systems has turned the conventional “passive” distribution network into an “active” one. In an active distribution network, some costumers not only consume electricity, but they also generate electricity and if their generation surpasses the power demand, these customers will then supply the excess to the network. Photovoltaic energy penetration in the Nigeria distribution network was modelled using ETAP Software in this work. Short circuit analysis was performed using symmetrical components while the power flow analysis of the network was done using the Newton-Raphson method.